"تأثير التسميد بعنصري البورون والزنك رشاً على الأوراق في بعض الخصائص المورفولوجية، والنسبة المئوية للبروتين على نبات الفول البلديViciafaba L (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2016)
This research carried out in Al- Bassa village at Lattakia province during 2013-2014, to determine the effects of increasing rates of boron and zinc fertilization by foliar spraying, on root nodulation and seed yield of broad beans (Viciafaba L.). Seeds were planted in plastic pots (15 kg capacity), filled with sandy-silty soil, characterized by its poor content of boron, and represents most of lands in the region. Boron and zinc were sprayed by five increasing concentrations (Bo, B25, B50, B75 and B100) and (Zno, Zn25, Zn50, Zn75, Zn10)on broad bean plants at 33 and 65 days post-emergent. Results showed that treatments high significance than control, in termsof root length witch the best treatment was B100Zn100with 31c.m, and 2.85 g for B75Zn75 as a wight of length, on the other hand the best treatment for number of nodules was B75Zn75, 179.03 c.m, B100Zn100 was the best for height of the plant with 100.20, for protein B100Zn100 the best with 37.4%, However, boron and zinc fertilization treatment B75Zn75 is the best, economically. نفذ البحث في قرية البصة التابعة لمحافظة اللاذقية في العام 2013-2014، لتحديد تأثير التسميد بمعدلات متزايدة من أسمدة البورون والزنك رشاً على الأوراق في تشكيل العقد الجذرية والغلة البذرية، ونسبة البروتين في بذور نبات الفول البلدي Viciafaba L.. زرعت التجربة في أصص بلاستيكية سعة 15 كغ، مملوءة بتربة سلتية رملية فقيرة المحتوى بالبورون، وممثلة لمعظم أراضي المنطقة، وتم رش البورون بخمسة تراكيز متزايدة (Bo, B25, B50, B75, B100)، والزنك بخمسة تراكيز أيضاً (Zno, Zn25, Zn50, Zn75, Zn100) على نباتات الفول بعد مرور 33 و65 يوماً من الإنبات. بينت النتائج أن جميع معاملات البورون والزنك والتداخل تتفوق معنوياً على الشاهد من حيث طول الجذر أفضل معاملة B100Zn100 بطول 31سم وللمعاملة B75Zn75 بالنسبة إلى الوزن الجاف للجذر2.85 غ،وبالنسبة إلى متوسط عدد العقد في المعاملة B75Zn75179.03 عقدة، وبالنسبة إلى طول النبات في المعاملة B100Zn100100.20سم ، أما بالنسبة إلى محتوى بذور النبات من البروتين فحققت المعاملة B100Zn100 أفضل نسبة 37.4% ، وكانت المعاملة B75Zn75 هي الأفضل من الناحية الاقتصادية.